2009
DOI: 10.1111/j.1610-0387.2008.06753.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin diseases in intensive care medicine

Abstract: Though most dermatoses are not life-threatening, skin diseases play an important role in intensive care medicine. Skin findings in intensive care patients may reflect the underlying disease or be complications of intensive medical care. Most important are drug reactions, infections, bacterial toxin reactions, erythroderma, ANCA-positive vasculitides (such as Wegener granulomatosis) and bleeding disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The development of dermatological problems in addition to the primary reason for admission to the ICU may bring about an extra burden of mild to severe complications in ICU-treated patients. The general health condition of the patients may worsen and the ICU length of stay is often extended [3,8]. The morphology and clinical progression of skin diseases may be atypical due to associated conditions such as medications administered to ICU patients, impaired immune function, edema and impaired tissue perfusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of dermatological problems in addition to the primary reason for admission to the ICU may bring about an extra burden of mild to severe complications in ICU-treated patients. The general health condition of the patients may worsen and the ICU length of stay is often extended [3,8]. The morphology and clinical progression of skin diseases may be atypical due to associated conditions such as medications administered to ICU patients, impaired immune function, edema and impaired tissue perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…The morphology and clinical progression of skin diseases may be atypical due to associated conditions such as medications administered to ICU patients, impaired immune function, edema and impaired tissue perfusion. Therefore, diagnosing and treating skin diseases in ICU patients may frequently cause a challenging problem for dermatologists [2,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…[2] Dermatological disorders are common problems at ICUs. [9] Our study revealed that the most common infectious dermatological disorder was wound infection, the most common drug reaction was maculopapular drug eruption, and the most common dermatosis was frictional dermatosis. We demonstrated that the presence of multiple comorbidities, HT, DM, CAD, Parkinson, and stroke was associated with increased prevalence of dermatological disorders.…”
Section: Discussionmentioning
confidence: 90%
“…Many studies to date have indicated that the prevalence of drug reactions among patients admitted to ICU was between 9.3% and 21.6%, with maculopapular drug rash being the most common type of rash. [46912] Although the main medication types causing drug reactions are antibiotics and chemotherapeutics, nonsteroidal anti-inflammatory drugs may also lead to a considerable proportion of drug reactions as reports have indicated. [9] The prevalence of drug reactions in our study was 45.2%, which was greater than what was previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation